Towards Integrating Realities - Pragmatic Constructivism and Arendt’s Theory of Action - Henriksen, Lars Bo (Proceedings of Pragmatic Constructivism, 2017)
The pragmatic constructivist approach provides us with a social science theory, the theory of reality, and its associated method, the conceptualising method. A key aspect in both the theory of reality and its associated conceptualising method is on the necessity of integrating four dimensions of reality – facts, logic, values and communication. But how? Nørreklit (2004) highlights the theoretical and methodological requirements for such integration of reality. Henriksen et al. (2004), on the other hand, describe the integration processes through a series of case stories. But a thorough conceptualisation of the process of integration is itself not analysed or conceptualised to the same substantive extent as are the other elements of the theory of reality. The key question addressed here therefore becomes: how might we better analyse and describe this process of integration? To address this question, I identify, albeit in skeletal outline, useful social theoretical correspondences between Arendt’s conceptualisation of action in The Human Condition (1958) and key attributes of the theory of reality, which, I claim, could possibly guide an entry into the ‘how’ of this elusive integration process.